A nanoporous diamond particle microelectrode and its surface modification. (20th October 2022) - Zhu, Ruitong; Deng, Zejun; Wang, Yijia; Zhou, Kechao; Yu, Zhiming; Ma, Li; Wei, Qiuping
Highlights: A simple and feasible way to fabricate a nanoporous BDD particle microelectrode. In situ surface modification of a single nanoporous BDD microparticle was described. The proposed electrode exhibited one order of magnitude higher k 0 than the bare one. A higher surface conductivity and larger ECSA was observed after modification. Abstract: Boron doped diamond electrode (BDDE) with dimensions of tens of or hundreds of μm has received widespread attention for electrochemical and biological applications because of exceptional features such as wide potential window for water stability, excellent electrochemical/chemical stability, and superior antifouling properties. This work reported a feasible way to fabricate a single nanoporous BDD particle microelectrode (sDPME) using a commercial single-crystal BDD particle (cBDD) as the substrate. The nanoporous surface of cBDD (pcBDD) was formed via thermal catalytic treatment with nickel as the catalyst, followed by further electrodeposition of gold nanoparticles (Au NPs) to fill the nanopores, increasing its electrocatalytic performance. As a comparison, the heavily-doped polycrystalline BDD film was deposited on cBDD via hot-filament chemical vapor deposition, increasing its electrical surface conductivity, followed by the similar thermal etching to form the nanoporous surface (prBDD) as well as Au NPs modification. We gradually characterized surface modification of cBDD using scanning electron microscopy, Raman, energy dispersive spectroscopy and various electrochemical techniques. The results demonstrated that among six sDPMEs, the Au NPs-modified nanoporous sDPMEs (Au/prBDD) have one order of magnitude higher heterogeneous electron transfer kinetic constant than the cBDD. This difference was attributed to synergistic effects of the improved electrical conductivity (with a higher doping level of few 10 20 cm −3 versus 10 18 cm −3 ), the improved capability for electron transfer (with lower charge transfer resistance of 1.3 kΩ versus 8.6 kΩ) as well as the increased electrochemically active surface area (1.12 mm 2 versus 0.34 mm 2 ). Graphical abstract: Image, graphical abstract